JOM: The Journal 2025-2026 Editorial Calendar Is Open for Submissions - Kelly Markel (JOM, 2024)
CONTEXT: Severe asthma affects 3-10 % of all asthma patients but accounts for disproportionately high morbidity and mortality. These patients tend to experience more frequent hospitalization compared to mild-to-moderate controlled asthmatics or the general population. Despite optimized inhaler therapy, many patients experience persistent symptoms and impaired lung function. Biologics targeting type-2 inflammation, including benralizumab, dupilumab, and tezepelumab, have emerged as add-on treatments that improve lung function and quality of life. Blood eosinophil count has been identified as a predictor of treatment response (i.e., ≥150 cells/µL). Although individual randomized controlled trials have evaluated these biologics separately, no prior meta-analysis has compared their effects within a unified framework or systematically examined whether treatment benefits differ by baseline eosinophil levels. OBJECTIVES: The objective of this meta-analysis was to evaluate the efficacy of benralizumab, dupilumab, and tezepelumab in adults with severe asthma. The primary outcome was the change in prebronchodilator forced expiratory volume in 1 s (FEV1). Secondary outcomes included the Asthma Control Questionnaire (ACQ) and Asthma Quality of Life Questionnaire (AQLQ) scores. Analyses were stratified by baseline blood eosinophil count (≥300 vs. <300 cells/μL), with interaction testing to determine whether eosinophil levels modify treatment response. METHODS: A systematic literature search identified phase 3 randomized controlled trials evaluating benralizumab, dupilumab, and tezepelumab in adults with severe asthma. Data were extracted from the SIROCCO, QUEST, and PATHWAY/NAVIGATOR trials. Pooled estimates were calculated utilizing a random-effects meta-analysis model. Continuous outcomes were summarized as mean differences with 95 % confidence intervals (CIs), and subgroup analyses were performed by baseline eosinophil count (≥300 vs. <300 cells/μL). Interaction was assessed utilizing Cochran's Q test for subgroup differences, with statistical significance defined as p<0.05. RESULTS: The pooled improvement in prebronchodilator FEV1 was 0.133 L (95 % CI, 0.107-0.159; p<0.001), exceeding the minimal clinically important difference (MCID) of 0.10 L. Effects were comparable across agents: benralizumab 0.130 L, dupilumab 0.132 L, and tezepelumab 0.135 L. The ACQ score improved by -0.293 (95 % CI, -0.358 to -0.227), and the AQLQ score increased by 0.283 (95 % CI, 0.214-0.351). Patients with eosinophils ≥300 cells/μL had greater FEV1 gains (0.201 L; 95 % CI, 0.165-0.237) than those with <300 cells/μL (0.057 L; 95 % CI, 0.023-0.090), with significant subgroup heterogeneity (p<0.001). CONCLUSIONS: All three biologics produced similar, clinically meaningful improvements in lung function. Higher baseline eosinophil counts predicted a greater response. Patient-reported outcomes improved modestly but did not reach MCID thresholds, possibly due to ceiling effects in patients already receiving maximal inhaler therapy.